Digital photographic measurements of the proximal femoral anatomy - Sarut Waranuchitkul (2019)
© 2018 Siriraj Medical Journal. Objective: This study evaluated the morphology of the proximal femur in the Thai population, especially the femoral head-neck relationship and the femoral neck-shaft relationship, using digital photographs. Methods: The morphology of each proximal femur was evaluated via the standard anteroposterior and cephalocaudal views of digital photographs. The femoral head-neck junction morphology was evaluated for translation, rotation, and concavity. The femoral neck-shaft anatomy was measured with the neck-shaft angle and the neck version. Results: Fifty-nine Thai femora with an average age of 45.4 years were evaluated. For the femoral head-neck translation, the average superior/inferior offset ratio was 1.01, and the average anterior/posterior offset ratio was 0.97. For the femoral head-neck rotation, the average anteroposterior and lateral physeal angles were 77.5° and 81.9°, respectively. Regarding the head-neck junction concavity, the average gamma, delta, alpha, and beta angles were 45.6°, 44.5°, 45.5°, and 36.2°, respectively. The average femoral neck-shaft angle was 129.5°, and the average femoral neck version was 5.7° of anteversion. Conclusion: Thai femora had their heads located almost at the center of the femoral neck, and they were rotated in abduction and anteversion relative to the neck axis. The femoral head-neck junctions showed less concavity anteriorly and superiorly.